Exchange Rate Volatility and Economic Growth In Nigeria - Dickson, Oyovwi O. (Richtmann Publishing, 2012)
This study seeks to evaluate the effect of exchange rate volatility on economic growth in Nigeria on the basis of annual datafrom 1970 to 2009. A review of the literature reveals that exchange rate volatility can have either positive or negative effect on economicgrowth. The empirical analysis began with testing for stationarity of the variables by applying the Augmented Dickey-Fuller (ADF). Thiswas followed by co-integration test of the model. The unit root test results show that all variables except exchange rate volatility wereintegrated at order one, that is I(1) while exchange rate volatility is integrated at order zero that is I(O). Also, co-integration analysisindicated that variables are co-integrated. Employing the Generalised Autoregressive Conditional Heteroscedasticity (GARCH) techniqueto generate exchange rate volatility, the relationship between exchange rate volatility and economic growth was estimated. Findingsfurther show that in the short run, economic growth is positively responsive to exchange rate volatility while in the long run, a negativerelationship exist between the two variables. The long run result also indicate that increase in oil price depress economic growth inNigeria. Thus, the income effect of rising oil price is not felt while the output effect is evidenced in factory closure and re-location toneighbouring countries. The study recommends control of import content of both public and private expenditure, greater diversification ofthe economy through investment in key productive sectors of the economy to guard against the vicissitude exchange rate volatility. Also,domestic refining of crude oil to avoid the current massive importation and in the short run, we recommend the legalisation of the refiningactivities in the creeks to supplement the existing refineries in the country.